Design & development of poka-yoke system for nut identification to defect prevention - Sarah Fathiah , Ali (2013)
Poka-yoke is a method in a lean manufacturing process that use sensor or other devices to avoid and eliminate product defects by preventing, correcting or drawing attention of human errors. The aim of this project is to design, develop and analyze Poka-yoke system for nut identification to defect prevention. The development Poka-yoke systems start with construct programming using Arduino IDE software and microcontroller ATmega328 is used as interface between the system and hardware. Next process is to build and implement the hardware using two proximity sensor named sensor 1 and 2 and trigger system. To validate this system, size and thickness of the nut and different specimen’s material are analyzed. Findings shows sensor 1 and 2 and trigger signal are working efficiency by detecting missing nut. It can conclude that Poka-yoke system is very flexible, simple and robust to detect and correct localization mistakes and it helps to reduce the number of error occurring during the production processes.